Analisis Perbaikan Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan pada UMKM Ngopi Pojok 98’s - I Made Bimas Cass Tanjung; Made Ayu Jayanti Prita Utami; I Wayan Wirga (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The increasing competition in the coffee shop industry requires Micro, Small, and Medium Enterprises (MSMEs) to continuously improve service quality and product quality to maintain customer satisfaction and business sustainability. Ngopi Pojok 98 experienced a decline in revenue over several months, indicating potential problems related to service performance and product consistency. This study aims to analyze the improvement of customer satisfaction after implementing service quality and product quality enhancements at Ngopi Pojok 98. This research employed a quantitative approach using a One Group Pretest–Posttest Design. The sample consisted of 50 respondents selected through purposive sampling. Data were collected using questionnaires administered before and after the improvement program and analyzed using validity tests, reliability tests, the Shapiro–Wilk normality test, and the Paired Sample t-Test with the assistance of SPSS software. The results showed that all instruments were valid and reliable. The normality test indicated a significance value of 0.291 (>0.05), confirming normal data distribution. Furthermore, the Paired Sample t-Test produced a significance value of 0.000 (<0.05), indicating a significant difference in customer satisfaction before and after the improvements. The average satisfaction score increased from 29.68 to 34.88. These findings confirm that enhancing service quality and product quality effectively improves customer satisfaction in coffee shop MSMEs.